2021
DOI: 10.3390/d13050190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Salinity Levels on Population Dynamics and Growth of the Cyclopoid Copepod Oithona nana

Abstract: Copepods are one of the most abundant and diverse live food sources for mesopelagic and bathypelagic fishes and crustaceans. They could contribute to the overlap of the transition period from live feed to an artificial weaning diet in marine larvae production. However, the culture conditions still need optimization to provide sufficient production to cover the increasing demand for marine hatcheries. Therefore, the present study investigated the effects of different salinity levels (5, 10, 15, 20, 25, and 30 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…At 15 ppt and 45 ppt, the percentage composition of adults and copepodites was higher due to the lack of naupliar production and poor survival rate. This also supports the findings of Magouz et al (2021), where a significantly higher percentage composition of nauplii and copepodites is reported in O. nana at the salinity levels from 20 to 30 ppt. There are various reports suggesting that higher the number of nauplii in a culture reflects the higher reproductive rate of the females which consequently enhances the final population (Vanderlugt et al, 2009; Wilson et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…At 15 ppt and 45 ppt, the percentage composition of adults and copepodites was higher due to the lack of naupliar production and poor survival rate. This also supports the findings of Magouz et al (2021), where a significantly higher percentage composition of nauplii and copepodites is reported in O. nana at the salinity levels from 20 to 30 ppt. There are various reports suggesting that higher the number of nauplii in a culture reflects the higher reproductive rate of the females which consequently enhances the final population (Vanderlugt et al, 2009; Wilson et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Nauplii of other cyclopoids like Dioithona rigida (Santhanam et al, 2018) and Oithona simplex (Noor et al, 2018) were reported to give better survival in lower salinities than the higher salinity ranges from the mean seawater salinity (35 ppt). Cyclopoids, particularly the members of Oithona and Dioithona , have better survival in lower salinities (Magouz et al, 2021). Salinity stress induces the degradation of more amino acids to meet the energy requirements for osmoregulation which in turn causes depletion in protein reserves and thereby adversely affects the survival of nauplii, especially the non‐feeding initial naupliar stages (Farmer & Reeve, 1978; Kimmel & Bradley, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is capable of consuming phytoplankton, bacteria, protozoa, and small crustaceans [ 47 , 48 ]. It can also consume yeast and flour from vegetable sources [ 7 , 46 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%